Establishment and characterization of new cell lines of anaplastic pancreatic cancer, which is a rare malignancy: OCUP-A1 and OCUP-A2. Issue 1 (December 2016) - Miura, Kotaro; Kimura, Kenjiro; Amano, Ryosuke; Yamazoe, Sadaaki; Ohira, Go; Murata, Akihiro; Nishio, Kohei; Hasegawa, Tsuyoshi; Yashiro, Masakazu; Nakata, Bunzo; Ohira, Masaichi; Hirakawa, Kosei
Abstract Background Anaplastic pancreatic cancer (APC) cell lines have been scarcely established. Methods The morphology, gene expressions, karyotyping and epithelial-mesenchymal transition markers of newly established APC cell lines OCUP-A1 and OCUP-A2 were analyzed. Their abilities of proliferation under normoxia and hypoxia, migration and invasion were compared to 4 commercially available pancreatic ductal adenocarcinoma (PDA) cell lines. Their induction of angiogenesis, stem-like cell population and subcutaneous tumor growth in nude mice were estimated, comparing 2 PDA cell lines examined here. Results OCUP-A1 and OCUP-A2 cells continuously grew with spindle and polygonal shapes, respectively. Gene analysis revealed 9 gene mutations including KRAS and TP53. Karyotyping clarified numerical structural abnormalities in both cells. Loss of E-cadherin and expression of vimentin in both cell lines were observed. The doubling time of both cell lines was approximately 20 h. Proliferation, migration and invasion abilities were not notable compared to other PDA cell lines. However stem-like cell population of both cell lines was superior to a part of PDA cell lines. Moreover OCUP-A1 showed stronger hypoxia tolerance and induction of angiogenesis than other PDA cell lines. The tumorigenicity in vivo of OCUP-A2 was stronger than conventional PDA cell lines. Conclusions The OCUP-A1 and OCUP-A2 cell lines of rare malignancies might be useful for investigating the biology of pancreatic cancer.